Moral, the Informal Sector, and Unemployment - Ann-Sofie Kolm; Birthe Larsen (Uppsala University, Department of Economics, 2001)
While examining the macroeconomic effects of increased government control of the informal sector, this paper develops a two-sector general equilibrium model featuring matching frictions, and heterogeneous workers in terms of moral. This facilitates an analysis of how wage setting and unemployment is affected by punishment policies, which is ignored in the previous literature.
Keywords: H26; 330; Tax evasion; wage bargains; matching; moral; unemployment; Arbeitsangebot; Informeller Sektor; Schattenwirtschaft; Kosten; Theorie